A holistic view of value generation process in a SSBI environment: a service dominant logic perspective. (15th May 2018) - Bani-Hani, Imad; Pareigis, Jorg; Tona, Olgerta; Carlsson, Sven
Abstract: Self-service business intelligence (SSBI) is an emerging trend in organisations allowing users to become more autonomous in data exploration. Organisations are keen to provide such services for their employees due to its potential benefits. However, there is little empirical knowledge about the process of building a SSBI service and the role of users in this process. From an exploratory single case study of a major Norwegian online marketplace and drawing on service-dominant logic as an analytical framework, we identify and explore two major phases of building a SSBI service: co-production and co-creation. Besides providing a rich description of these phases, this study also explores the way stakeholders are involved and embedded throughout the process of value generation.